2008
DOI: 10.1016/j.hrthm.2007.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Markers of inflammation before and after curative ablation of atrial flutter

Abstract: CRP and IL-6 levels are elevated in patients presenting in AFL. Given the lower CS values in these patients, their origin appears to be systemic rather than cardiac. Because these levels significantly fall after ablation of AFL, the atrial tachyarrhythmia appears to be the cause (not the effect) of the inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 23 publications
7
49
0
Order By: Relevance
“…The relationship between IL-6 and AF may be mediated by left atrial enlargement. 269 While evidence that inflammatory markers presage the development of AF has been replicated, 268,274 there are also multiple studies to demonstrate that atrial arrhythmias likely contribute to inflammation: specifically, cardioversion of AF 275 as well as ablation of either AF 276 or atrial flutter 277 has resulted in a decrease in inflammation. Indeed, Marcus et al demonstrated that the rhythm at the time of the blood draw (AF vs. sinus) was an important determinant in detecting an elevated CRP or IL-6 level.…”
Section: Impact Of Atrial Cardiomyopathies On Occurrence Of Atrial Fimentioning
confidence: 99%
“…The relationship between IL-6 and AF may be mediated by left atrial enlargement. 269 While evidence that inflammatory markers presage the development of AF has been replicated, 268,274 there are also multiple studies to demonstrate that atrial arrhythmias likely contribute to inflammation: specifically, cardioversion of AF 275 as well as ablation of either AF 276 or atrial flutter 277 has resulted in a decrease in inflammation. Indeed, Marcus et al demonstrated that the rhythm at the time of the blood draw (AF vs. sinus) was an important determinant in detecting an elevated CRP or IL-6 level.…”
Section: Impact Of Atrial Cardiomyopathies On Occurrence Of Atrial Fimentioning
confidence: 99%
“…Fustaci et al demonstrated that marked inflammatory infiltrates in the atrial biopsies of patients with lone AF 17 . Additionally, previous studies concluded a decrease in inflammation after cure of atrial arrhythmias 15,18 . The results of all these previous studies suggested that atrial tachyarrhythmia's may be responsible for or at least stimulate a systemic inflammatory process.…”
Section: Resultsmentioning
confidence: 92%
“…The literature contains only limited data from small-scale studies assessing the diagnostic values of biomarkers in patients presenting to the ED with SVT [12][13][14] . Previous studies concluded that inflammation may play an important role in SVT 15,16 . Chung et all concluded that an elevated inflammation markers (specially Creactive protein) may predict atrial tachycardia's in some patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients medicated with statins tended to include younger patients, whereas those medicated with ACE-Is or AII antagonists tended to include older patients with hypertension or a reduced ventricular function; which may have modified the results of the analysis of our data. Recent clinical studies have demonstrated that the CRP level is transiently elevated after CA (Marcus et al 2008), and that the short-term AF episodes were transiently increased (Oral et al 2002). These reports also suggested that the increased inflammatory response from the CA procedure may increase the following transient occurrences of AF.…”
Section: Anti-inflammatory Agents For Preventing Af Occurrencesmentioning
confidence: 97%